Pituitary adenylate cyclase-activating polypeptide (PACAP) mimics neuroendocrine and behavioral manifestations of stress: Evidence for PKA-mediated expression of the corticotropin-releasing hormone (CRH) gene - Agarwal, Anika; Halvorson, Lisa M.; Legradi, Gabor (Brain research. Molecular brain research., 2005)
The physiologic response to stress is highly dependent on the activation of corticotropin-releasing hormone (CRH) neurons by various neurotransmitters. A particularly rich innervation of hypophysiotropic CRH neurons has been detected by nerve fibers containing the neuropeptide PACAP, a potent activator of the cAMP-protein kinase A (PKA) system. Intracerebroventricular (icv) injections of PACAP also elevate steady-state CRH mRNA levels in the paraventricular nucleus (PVN), but it is not known whether PACAP effects can be associated with acute stress responses. Likewise, in cell culture studies, pharmacologic activation of the PKA system has stimulated CRH gene promoter activity through an identified cAMP response element (CRE); however, a direct link between PACAP and CRH promoter activity has not been established. In our present study, icv injection of 150 or 300 pmol PACAP resulted in robust phosphorylation of the transcription factor CREB in the majority of PVN CRH neurons at 15 to 30 min post-injection and induced nuclear Fos labeling at 90 min. Simultaneously, plasma corticosterone concentrations were elevated in PACAP-injected animals, and significant increases were observed in face washing, body grooming, rearing and wet-dog shakes behaviors. We investigated the effect of PACAP on human CRH promoter activity in αT3-1 cells, a PACAP-receptor expressing cell line. Cells were transiently transfected with a chloramphenicol acetyltransferase (CAT) reporter vector containing region − 663/+124 of the human CRH gene promoter then treated for with PACAP (100 nM) or with the adenylate cyclase activating agent, forskolin (2.5 μM). Both PACAP and forskolin significantly increased wild-type hCRH promoter activity relative to vehicle controls. The PACAP response was abolished in the CRE-mutant construct. Pretreatment of transfected cells with the PKA blocker, H-89, completely prevented both PACAP- and forskolin-induced increases in CRH promoter activity. Furthermore, CREB overexpression strongly enhanced PACAP-mediated stimulation of hCRH promoter activity, an effect which was also lost with mutation of the CRE. Thus, we demonstrate that icv PACAP administration to rats under non-stressed handling conditions leads to cellular, hormonal and behavioral responses recapitulating manifestations of the acute stress response. Both in vivo and in vitro data point to the importance of PACAP-mediated activation of the cAMP/PKA signaling pathway for stimulation of CRH gene transcription, likely via the CRE.